Appropriating Marivaux: The first English translations of La Vie de Marianne and Le Paysan Parvenu and the critical rivalry between Richardson and Fielding (1736-1750) - Baudouin MILLET (E-REA)
Marivaux’s last two novels La Vie de Marianne (1731-1742) and Le Paysan parvenu (1734-1735) began to be “Englished” while they were still in the making. As early as 1736 and 1735, the first instalments of both novels were translated into English versions which rather faithfully reproduced Marivaux’s initial prefaces and incipits. It seems that the publications of Richardson’s Pamela (1740) and Fielding’s Joseph Andrews (1742) aroused fresh interest in Marivaux’s works among new translators who drastically altered Marivaux’s initial paratexts, re-imagining (and thus re-presenting to readers) the French novels in different guises. Two new versions of Marianne’s story invested Richardson’s critical discourse on his novel and transposed it in their front materials, while the new translation of the adventures of Marivaux’s peasant borrowed critical ideas from Fielding’s reflective statements on his works in order to dress Jacob’s story in a completely new garb. Simultaneously, Marianne and Jacob were significantly rebaptized as Indiana and Sir Andrew Thompson, thereby directly gesturing towards Pamela and Joseph Andrews’s own names.